Immunomodulatory Effects of Colistin on Macrophages in Rats by Activating the p38/MAPK Pathway - Wang, Jin; Shao, Weili; Niu, Hui; Yang, Tianli; Wang, Yuning; Cai, Yun (Frontiers in Pharmacology, 2019)
Objectives: Colistin has been identified in a Caenorhabditis elegans chemical screening as an immunostimulatory agent that activates the conserved p38/PMK-1 pathway and provides protection against pathogens. Here we aimed to extend those findings to a mammalian model and evaluate the immunomodulatory effects of colistin on rat macrophages. Methods: Macrophages were isolated from SD rat. The effects of colistin on the cytokine secretion, phagocytic activity and protein expression were determined by ELISA, flow cytometry and Western blotting analysis, respectively. The relative microRNA expression was determined by microarray, and KEGG was used to identify potential signaling pathways. Results: Our data showed that 5, 10 and 20 µg/mL colistin significantly increased the secretion of TNF-α, while 20 µg/mL and 5 µg/mL colistin significantly increased the levels of IL-1β and IL-6, respectively. Flow cytometry results showed that the relative mean fluorescence intensity and percentage of phagocytosis in colistin treatment groups were significantly higher compared with the control group, while the increased phagocytosis phenomenon can be blocked by p38 inhibitor. The phagocytic ability of macrophages against S. aureus was significantly increased after colistin treatment. Microarray and KEGG pathway analyses revealed that mitogen-activated protein kinase (MAPK), mammalian target of rapamycin (mTOR), chemokine and B cell receptor were the main pathways involved in the colistin stimulation process. Western blotting analysis demonstrated that the phosphorylated p38 protein level of colistin treatment groups was increased in a dose dependent manner. Conclusions: Present study is the first to demonstrate that colistin had immunomodulatory effects on macrophages in mammals, and the p38/MAPK pathway was involved in such colistin-induced immunomodulatory effect.